2012
DOI: 10.1002/dneu.20998
|View full text |Cite
|
Sign up to set email alerts
|

Pathways for plasmalemmal repair mediated by PKA, Epac, and cytosolic oxidation in rat B104 cells in vitro and rat sciatic axons ex vivo

Abstract: Plasmalemmal repair (sealing) is necessary for survival of damaged eukaryotic cells. Ca(2+) influx through plasmalemmal disruptions activates pathways that initiate sealing, which is commonly assessed by exclusion of extracellular dye. These sealing pathways include PKA, Epac, and cytosolic oxidation. In this article, we investigate whether PKA, Epac, and/or cytosolic oxidation, activate specific proteins required to produce a plasmalemmal seal. We report that toxin cleavage of proteins required for neurotrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 40 publications
(101 reference statements)
3
32
0
Order By: Relevance
“…Considering the actions of EPAC on neuronal differentiation, the functions of specific activators and inhibitors of EPACs are becoming an attractive idea for therapies targeting neuronal injuries. For example, plasmalemmal repair is essential for neurons to maintain circuit connections postinjury (764,971). This repair process is accomplished by merging undamaged membranes (263, 970) through myelin delamination (52) and calcium-dependent accumulation of vesicles and undamaged membrane (262,558,858,1031).…”
Section: Neurite Development and Differentiationmentioning
confidence: 99%
“…Considering the actions of EPAC on neuronal differentiation, the functions of specific activators and inhibitors of EPACs are becoming an attractive idea for therapies targeting neuronal injuries. For example, plasmalemmal repair is essential for neurons to maintain circuit connections postinjury (764,971). This repair process is accomplished by merging undamaged membranes (263, 970) through myelin delamination (52) and calcium-dependent accumulation of vesicles and undamaged membrane (262,558,858,1031).…”
Section: Neurite Development and Differentiationmentioning
confidence: 99%
“…Epac, exchange protein activated by cAMP; DAG, diacylglycerol; PKA, phosphokinase A; PKC, phosphokinase C; PKI, phosphokinase in hibitor. Modified and used with permission from Spaeth et al ().…”
Section: Peg and Hypotonic Calcium‐free Salines Can Artificially Indumentioning
confidence: 99%
“…Two decades of research has subsequently revealed that, in more than 20 preparations studied to date, all eukaryotic cells (including neurons) seal plasmalemmal damage by Ca 2+ ‐dependent production of vesicles that form a plug, often at a partially constricted cut end (Krause et al, ; Steinhardt et al, ; Bi et al, ; Eddleman et al, ; Bittner and Fishman, ; Detrait et al, ; Yoo et al, ; Nguyen et al, ; McNeil, ; Spaeth et al, ; Zuzek et al, ; Jimenez et al, ). Vesicles from nearby intact membrane (Eddleman et al, ), lysosomes (Reddy et al, ), and/or myelin delaminations (Ballinger et al, ) migrate, accumulate, and pack tightly at the damage site to seal small holes within seconds to minutes and to seal complete axonal transections within 5–20 min (Fig.…”
Section: Nerve Axons and Other Eukaryotic Cells Repair (Seal) Plasmalmentioning
confidence: 99%
See 2 more Smart Citations